Air Pollution and Cognitive Development at Age 7 in a Prospective Italian Birth Cohort. Issue 2 (March 2016) - Porta, Daniela; Narduzzi, Silvia; Badaloni, Chiara; Bucci, Simone; Cesaroni, Giulia; Colelli, Valentina; Davoli, Marina; Sunyer, Jordi; Zirro, Eleonora; Schwartz, Joel; Forastiere, Francesco
Abstract : Background: Early life exposure to air pollution has been linked with cognitive impairment in children, but the results have not been conclusive. We analyzed the association between traffic-related air pollution and cognitive function in a prospective birth cohort in Rome. Methods: A cohort of 719 newborns was enrolled in 2003–2004 as part of the GASPII project. At age 7 years, 474 children took the Wechsler Intelligence Scale for Children-III to assess their cognitive development in terms of IQ composite scores. Exposure to air pollutants (NO2, PMcoarse, PM2.5, PM2.5 absorbance) at birth was assessed using land use regression models. We also considered variables indicating traffic intensity. The effect of environmental pollution on IQ was evaluated performing a linear regression model for each outcome, adjusting for gender, child age at cognitive test, maternal age at delivery, parental educational level, siblings, socio-economic status, maternal smoking during pregnancy, and tester. To account for selection bias at enrollment and during follow-up, the regression models were weighted for the inverse probabilities of participation and follow-up. Results: A 10 μg/m 3 higher NO2 exposure during pregnancy was associated with 1.4 fewer points (95% confidence interval = −2.6, −0.20) of verbal IQ, and 1.4 fewer points (95% confidence interval = −2.7, −0.20) of verbal comprehension IQ. Similar associations were found for traffic intensity in a 100 m buffer around home. Other pollutants showed negative associations with larger confidence intervals. Conclusions: Consistent with previous evidence, this study suggests an association of exposure to NO2 and traffic intensity with the verbal area of cognitive development. See Video Abstract athttp://links.lww.com/EDE/B12 . Abstract : Supplemental Digital Content is available in the text.